Adiabatic temperature change, magnetic entropy change and critical behavior near the ferromagnetic–paramagnetic phase transition in La0.7(Ca, Sr)0.3MnO3 perovskite. (3rd July 2018) - Riahi, K.; Messaoui, I.; Ezaami, A.; Cugini, F.; Solzi, M.; Cheikhrouhou-Koubaa, W.; Cheikhrouhou, A.
ABSTRACT: A systematic study of the magnetocaloric effect in La0.7 Ca0.15 Sr0.15 MnO3 perovskite has been performed by both direct and indirect measurement techniques. In particular, the adiabatic temperature change has been measured by a purpose-built probe suitable for laboratory-scale samples, while magnetic measurements were carried out by standard magnetometric techniques. The observation of the effective behavior of the studied systems in adiabatic conditions and the significant value of the isothermal entropy variation indicate that La0.7 Ca0.15 Sr0.15 MnO3 could be considered as a potential candidate for application in magnetic refrigeration around room temperature. Moreover, the critical exponents (γ, β andδ ) determined using the Kouvel–Fisher method, the modified Arrott plot and the critical isotherm analysis are in good agreement with the theoretical prediction of the 3D-Ising model, indicating that the magnetic interactions are of short-range nature.